PENYULUHAN NILAI GUNA REKAM MEDIS DI RUMAH SAKIT UMUM DELI MEDAN - Desmayanti - Surbakti; Sri Sudewi Sitio; Andreas Lewis; evfy Septriani Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
A hospital is a healthcare institution offering comprehensive individual healthcare services, encompassing inpatient, outpatient, and emergency care. These healthcare facilities maintain medical records that consist of documentation and files comprising patient identification, examination results, administered treatments, as well as other procedures and services delivered to patients. The primary purposes of medical records are to facilitate healthcare and treatment, serve as legal evidence when necessary, establish the foundation for healthcare service financing, and contribute to health-related statistical analyses. The objective of this awareness campaign is to enhance healthcare professionals' comprehension of the significance of thorough medical records and to aid healthcare workers in accurately completing medical record documents at Deli Medan General Hospital.